2021
DOI: 10.3201/eid2701.203515
|View full text |Cite
|
Sign up to set email alerts
|

Waning Antibody Responses in Asymptomatic and Symptomatic SARS-CoV-2 Infection

Abstract: We investigated the kinetics of severe acute respiratory syndrome coronavirus 2 neutralizing antibodies in 7 asymptomatic persons and 11 patients with pneumonia. The geometric mean titer of neutralizing antibodies declined from 219.4 at 2 months to 143.7 at 5 months after infection, indicating a waning antibody response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
121
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 10 publications
23
121
1
3
Order By: Relevance
“…At the late stage, the antibody response, which was shown to be affected adversely by methylprednisolone in our study, might The anti-RBD antibody response was found to be affected modestly in hamsters treated with remdesivir. This is generally consistent with the findings that the production of neutralizing antibodies was less robust in asymptomatic carriers of SARS-CoV-2 and patients with mild COVID-19 compared to those who develop a severe disease [42][43][44]. In contrast, the anti-RBD antibody response was much more severely compromised in hamsters treated with methylprednisolone alone, indicating its strong immunosuppressive effect [18].…”
Section: Discussionsupporting
confidence: 86%
“…At the late stage, the antibody response, which was shown to be affected adversely by methylprednisolone in our study, might The anti-RBD antibody response was found to be affected modestly in hamsters treated with remdesivir. This is generally consistent with the findings that the production of neutralizing antibodies was less robust in asymptomatic carriers of SARS-CoV-2 and patients with mild COVID-19 compared to those who develop a severe disease [42][43][44]. In contrast, the anti-RBD antibody response was much more severely compromised in hamsters treated with methylprednisolone alone, indicating its strong immunosuppressive effect [18].…”
Section: Discussionsupporting
confidence: 86%
“…Another interesting point to discuss at the epidemiological level is the waning antibody level in asymptomatic and symptomatic SARS-CoV-2 infections. Different studies have reported this decrease in the months following infection [36][37][38]. Most convalescent people who recover from COVID-19 do not have high levels of neutralizing activity.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that an asymptomatic infection might result in weaker protection [28]. We assume that naturally and vaccine-induced immunity will be long lasting, but some studies suggest that it might last only a few months [29]. If immunity is short-lived, then the results would be valid only for that time frame.…”
Section: Discussionmentioning
confidence: 99%